2009
DOI: 10.1007/s10298-008-0358-3
|View full text |Cite
|
Sign up to set email alerts
|

L’extrait huileux au CO2 supercritique de baies et de graines d’argousier (Hippophae rhamnoides L.) et ses effets sur la peau et les muqueuses

Abstract: Article original Pharmacognosie L'extrait huileux au CO 2 supercritique de baies et de graines d'argousier (Hippophae rhamnoides L.) et ses effets sur la peau et les muqueuses F. Joanny Menvielle-Bourg, Docteur en pharmacie FABIENNE JOANNY Consulting & Licensing 230, rue du Faubourg Saint-Honoré,Résumé : L'extrait huileux d'argousier obtenu selon la technique du CO 2 supercritique combine les actifs des graines et de la pulpe des baies : caroténoïdes, tocophérols, phytostérols et acides gras insaturés, notamme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Some fixed vegetable oils extracted by various processes (solvent, supercritical CO 2 , and cold pressure) have been proven to heal skin wounds [4852]. In a previous work, we showed the effectiveness of Opuntia ficus indica oil (OFI oil) extracted by cold pressing on the healing of full-thickness skin injury, as well as its antimicrobial effect against bacteria, yeast, and fungi [53].…”
Section: Introductionmentioning
confidence: 99%
“…Some fixed vegetable oils extracted by various processes (solvent, supercritical CO 2 , and cold pressure) have been proven to heal skin wounds [4852]. In a previous work, we showed the effectiveness of Opuntia ficus indica oil (OFI oil) extracted by cold pressing on the healing of full-thickness skin injury, as well as its antimicrobial effect against bacteria, yeast, and fungi [53].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that by the end of ripening, the enzymatic activity of phytosterol biosynthesis stops in fruits. During this period, the phytosterols are no longer synthesized but are converted into other compounds [44]. The total phytosterol content was 128.56 ± 2.40 mg/100 g in the HEAI, reflecting a high concentration of dietary phytosterols that could efficiently reduce the cholesterol level in the blood [25,42].…”
Section: Chromatographic Characterization Of Phytosterols By Gc-msmentioning
confidence: 99%
“…It was reported that by the end of ripening, the enzymatic activity of phytosterol biosynthesis stops in fruits. During this period, the phytosterols are no longer synthesized but are converted into other compounds [44].…”
Section: Chromatographic Characterization Of Phytosterols By Gc-msmentioning
confidence: 99%